A novel wideband, high-performance slot-free CPW-fed antenna with a double-layer PBG structure featuring quasi-periodic and large holes for short-link terahertz applications - Nasredine Boujmil; Mohammed Fattah; Mohammed Mahfoudi; Wafae El Hamdani; Said Mazer; Moulhime El Bekkali (Scientific African)
The increasing demand for 6G technology, which requires faster data rates and high-capacity transmission, is driving research into the terahertz (THz) spectrum, necessitating the development of compact, wideband, and directive antennas. Typical antenna configurations struggle to provide the bandwidth and power efficiency for emerging THz applications due to complex design challenges. As these limitations directly impact 6G performance, innovative approaches are needed. To address this issue, this study proposes a novel compact coplanar waveguide (CPW) antenna incorporating a slot-free double-layer photonic bandgap (PBG) structure in the substrate, unprecedented in THz literature. The design features a rectangular patch with bottom diagonal edge cuts and a double-layer PBG structure in the polyimide substrate, consisting of quasi-periodic circular air holes to enhance bandwidth and impedance matching. With a frequency range of 0.1–1 THz and physical size of 960 μm × 960 μm × 75 μm, the final THz antenna provides a low reflection coefficient of -52 dB, a maximum gain of 12.5 dBi, a bandwidth of 870 GHz and a radiation efficiency of 99.43 %. These performance results, combined with the practical feasibility of the slot-free design, directly answer the need for high data rates and energy efficiency required for emerging 6G applications in the terahertz spectrum.